Bibliography of The Publication on The History of The Ancient Oasis - Bayturaev T. D.; Khudaiberdieva Z. M.; Abraev Z. (Web of Journals Publishing, 2023)
This article studies a scientific auxiliary bibliographic index on the history of the city of Khiva and the Khorezm region. The article reveals the significance of the bibliography of published books, articles, manuscripts on economics, culture, science, art, the history of the topography of this city and the Khorezm region. The list of literature of this index can be recommended to specialists on this subject and to a wide range of readers who are interested in the history and cultural life of the population of the city of Khiva. The reader's address of the publication on education, health care, culture, art, history, urban planning is also determined.
Keywords: city, economy, architecture, publications, bibliography, knowledge, education.